Study on Strength and Durability Characteristics of Hybrid Fibre Reinforced Self-Healing Concrete - Subhashini, S.; K.Yaswanth, K.; S.V.Prasad, D (International Journal of Engineering and Technology, 2018)
The main disadvantage of using concrete, which is accepted to be irreplaceable building material, is the formation of micro cracks. This is due to the fact that concrete is weak in tension. To arrest the microcracks developed in the concrete and to eliminate the drawbacks due to microcracks, the recent trend in the innovation of the concrete is the usage of self-healing concrete or bacterial concrete. It is based on the principle that; the bacteria present in the moisture of the concrete repairs or heals the cracks on the concrete. Another recent advancement in the field of concrete technology is the usage of the fibres in the concrete. It not only arrests the cracks in the concrete but also increases the strength and durability characteristics and also it reduces the quantity of cement to some extent. This paper tries to attempt the usage of hybrid fibres along with the self-healing concrete to enhance the desirable characteristics of hybrid fibres as well as bacterial concrete. This experimental programme investigates the concrete on its strength and durability characteristics.Â Â